2021
DOI: 10.1155/2021/5549006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tai Chi Chuan on Emotional Health: Potential Mechanisms and Prefrontal Cortex Hypothesis

Abstract: Deep involvement in the negative mood over long periods of time likely results in emotional disturbances/disorders and poor mental health. Tai Chi Chuan (TCC) is regarded as a typical mind-body practice combining aerobic exercise and meditation to prevent and treat negative mood. Although there are an increasing number of TCC studies examining anxiety, depression, and mental stress, the mechanisms underlying these negative emotions are not fully understood. This review study examined TCC studies related to emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 105 publications
0
26
0
2
Order By: Relevance
“…Previous studies showed that TCC had obvious advantages in comparison with traditional rehabilitation methods (Luo et al, 2020 ; Galantino, Callens, Cardena, Piela, & Mao, 2013 ;. Yao, Ge, & Yu et al, 2021 ). First, TCC can utilize a flexible choice of exercise site and does not need any special equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that TCC had obvious advantages in comparison with traditional rehabilitation methods (Luo et al, 2020 ; Galantino, Callens, Cardena, Piela, & Mao, 2013 ;. Yao, Ge, & Yu et al, 2021 ). First, TCC can utilize a flexible choice of exercise site and does not need any special equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that exercise can enhance the functional connectivity between the posterior cingulate and the precuneus (Chirles et al, 2017 ). Tai Chi Chuan is a “moving meditation” (Yao et al, 2021 ). It involves elements of mindfulness and meditation that constantly guide the individual to focus on himself (breathing, movement, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, these exercise modalities are found to provoke different structural and functional changes in brain regions associated with executive function, memory, and visuospatial processing in healthy adults 19 , 20 . Common brain adaptation patterns are also found between individuals well-trained in Tai Chi and their counterparts practicing meditation or conventional exercise alone 21 . Meditation alone is beneficial to memory and cognitive flexibility, which is a subdomain of executive function 22 , hence it is conceivable that the meditation element of Tai Chi can augment the effects of the physical exercise element on various cognitive domains or subdomains.…”
Section: Introductionmentioning
confidence: 99%